2011
DOI: 10.1097/nmc.0b013e3182057a13
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Profiles of American Women in the Third Trimester

Abstract: Purpose To develop a profile of common nutritional patterns among pregnant, African American women that will assist providers in identifying areas for improvement and change. Study Design This study was part of a larger NIH funded (R03NR008548-01) study that examined risk factors associated with preterm labor and birth in high risk and low risk African American women. Data were collected on high risk mothers (women experiencing preterm labor) prior to 34 weeks gestation and every four weeks until delivery. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…These findings are consistent with those reported by Siega-Riz and Popkin (47) who evaluated nutrient intakes in women of childbearing age and with low socio-economic status, from 1977 to 1996. Gennaro et al (48) also reported that intakes of several micronutrients and protein from foods were inadequate among African-American women during pregnancy. Tinker et al (49) reported that of the~24 % of women of childbearing age meeting recommended usual intakes of folic acid, the majority were Whites, followed by Mexican Americans and African Americans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with those reported by Siega-Riz and Popkin (47) who evaluated nutrient intakes in women of childbearing age and with low socio-economic status, from 1977 to 1996. Gennaro et al (48) also reported that intakes of several micronutrients and protein from foods were inadequate among African-American women during pregnancy. Tinker et al (49) reported that of the~24 % of women of childbearing age meeting recommended usual intakes of folic acid, the majority were Whites, followed by Mexican Americans and African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Gennaro et al . ( 48 ) also reported that intakes of several micronutrients and protein from foods were inadequate among African-American women during pregnancy. Tinker et al .…”
Section: Discussionmentioning
confidence: 99%
“…Gennaro and colleagues (2011) similarly found Black women to be consuming inadequate micronutrients, including iron, vitamin D, and calcium, during the third trimester, but did not look to the second trimester to see if this was a consistent trend. Prenatal vitamins were not enough to completely supplement the lack of micronutrients consumed from food sources for the women in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of Black women in the third trimester, participants tended to have higher caloric diets with excessive fats, carbohydrates, and sugar that lacked important nutrients such as folate and fiber. The researchers did not test for consistency of this pattern earlier in pregnancy (Gennaro, Biesecker, Fantasia, Nguyen, & Garry, 2011). Brooten and colleagues (2012) examined diet in the first 20 weeks of pregnancy and found African American women consumed higher calorie diets than other racial groups, but they only examined diet at one time point.…”
Section: Calloutmentioning
confidence: 99%
“…In a study of American women who were in the third trimester of pregnancy, it was shown that Black women tended to have higher caloric intake, consuming foods rich in fats, carbohydrates, and sugar and poor in important nutrients, such as folate and fiber. 28 The head of household association and the consumption of healthier foods may demonstrate social inequalities, since female-headed households are largely associated with situations of economic vulnerability, in which women often end up in domestic activities and care of the offspring, which, in turn, results in greater difficulties to guarantee the subsistence of their own family, already with part-time affected generates dependency in low-paid jobs. 29 Receiving information about healthy food during prenatal care was highlighted among women who had the highest consumption of minimally-processed foods, as recommended in the pregnant woman's booklet, which states that to have a healthy pregnancy the pregnant woman should seek to have a diet rich in natural foods and poor in processed foods, in favor of maternal well-being, growth, and adequate training of the fetus.…”
Section: Discussionmentioning
confidence: 99%